Chromoselective Photocatalysis: Controlled Bond Activation through Light-Color Regulation of Redox Potentials - Ghosh, Indrajit; König, Burkhard (Angewandte Chemie International Edition, 2016)
Catalysts that can be regulated in terms of activity and selectivity by external stimuli may allow the efficient multistep synthesis of complex molecules and pharmaceuticals. Herein, we report the light‐color regulation of the redox potential of a photocatalyst to control the activation of chemical bonds. Light‐color control of the redox power of a photocatalyst introduces a new selectivity parameter to photoredox catalysis: Instead of changing the catalyst or ligand, alteration of the color of the visible‐light irradiation adjusts the selectivity in catalytic transformations. By using this principle, the selective activation of aryl–halide bonds for C−H arylation and the sequential conversion of functional groups with different reduction potentials is possible by simply applying different colors of light for excitation of the photocatalyst. I see your two colors, shining through: The xanthene dye rhodamine 6G is a moderately reducing photoredox catalyst if irradiated with green light, but provides an high reduction power of −2.4 V vs. SCE upon blue‐light irradiation. This allows control of the selectivity of photocatalytic C−H arylation reactions through changing the color of the light.